Phytotoxic Activity of Sesquiterpene Lactones-Enriched Fractions from Cynara cardunculus L. Leaves on Pre-Emergent and Post-Emergent Weed Species and Putative Mode of Action - Daniela Rosa; Carlos Rial; Teresa Brás; Rosa M. Varela; Francisco A. Macías; Maria F. Duarte (Plants, 2024)
Sesquiterpene lactones (SLs) are compounds that are highly produced in Cynara cardunculus leaves, known for their phytotoxic activity. This study aims to assess SL-enriched fractions’ (cynaropicrin, aguerin B, and grosheimin) phytotoxic potentials and putative modes of action, compared to an initial extract, using two approaches: first, against a panel of nine weed species in pre-emergence, and then on Portulaca oleracea L.’s post-emergency stage. The SL-enriched fractions demonstrated greater phytotoxic activity when compared with the C. cardunculus leaf initial extract. The SL-enriched fractions had higher activity at root growth inhibition over the panel tested, doubling the activity in five of them at 800 ppm. Regarding the post-emergence bioassay, the SL-enriched fractions had a higher influence on the plants’ growth inhibition (67% at 800 ppm). The SL-effects on the plants’ metabolisms were evidenced. The total chlorophyll content was reduced by 65% at 800 ppm. Oxidative stress induction was observed because of the enhancement in MDA levels at 800 ppm compared to control (52%) and the decrease in SOD-specific activity from 4.20 U/mg protein (400 ppm) to 1.74 U/mg protein (800 ppm). The phytotoxic effects of the SL-enriched fractions suggest that they could be used for a future bioherbicide development.